Application of earthworm and silicon can alleviate antibiotic resistance in soil-Chinese cabbage system with ARGs contamination. (15th February 2023) - Xiao, Zufei; Han, Ruixia; Su, Jianqiang; Zhu, Zhe; Zhao, Yi; Chen, Qinglin; Zhao, Junyi; Li, Gang; Zhu, Yong-Guan
Abstract: Organic fertilization is a major contributor to the spread of antibiotic resistance genes (ARGs) in the agroecosystem, which substantially increases the risk of ARGs acquisition and their transmission into human food chains. Earthworms are among the most vital soil faunas involved in the link between belowground and aboveground, and silicon is beneficial for soil health and plant stress resistance. This study aims to explore the effect of different amendment strategies (earthworm and/or silicon) and the related influencing factors on the alleviation of ARGs using high-throughput qPCR. The results showed that the application of earthworms and silicon fertilizers reduced the absolute abundance of ARGs in the rhizosphere soils, either singly or in combination. According to the structural equation model and random forest analysis, mobile genetic elements are the major factors enhancing ARGs transfers and the treatment affects ARGs in direct or indirect ways. Our results highlight the role of "rhizosphere effect" in alleviating antibiotic resistance and suggest that silicon fertilizers, together with the earthworms, can be considered as a sustainable and natural solution to mitigate high-risk ARGs spread in the soil-plant systems. Our findings provide guidance in formulating strategies for halting the spread of ARGs in the agroecosystem. Graphical abstract: Image 1 Highlights: The application of earthworm alleviated Rank I ARGs in the soil-plant system. The addition of silicon effectively alleviated ARGs in the soil-plant system. Rank I ARGs enrichment in phyllosphere reduced significantly after all treatments. Combined application alleviated the ARGs transmission in the soil-plant system.